Emerging Themes, Leaders, and Collaboration in Library and Information Science Research - Wattanasiri, Pornnisa; Manorom, Paiboon; Chansanam, Wirapong (Data and Metadata, 2025)
Introduction: This study uses bibliometric methods to evaluate research articles within the library and information science (LIS) domain. The focus is to uncover trends and patterns in social network analysis related to LIS, particularly examining research collaborations and content within highly cited articles. By analyzing these aspects, the study seeks to identify influential authors, prominent research themes, and key contributors in the LIS field. Methods: A dataset of 14,517 articles published between 1954 and 2023 was extracted from the Scopus database for bibliometric analysis. The study concentrated on publications in the LIS domain, focusing on the journal Library Philosophy and Practice. Multiple Correspondence Analysis (MCA) was used to identify clusters within the research field, while content analysis was performed to determine prevalent topics and disciplinary influences within the articles. Results: The analysis revealed that China is home to many of the most influential authors in the LIS domain, with the United States, China, and the United Kingdom identified as the top contributing countries to LIS research. Common research themes include information science, bibliometrics, academic libraries, information literacy, and LIS education. Two main clusters emerged from the MCA: one focused on information-related concepts and the other on bibliometrics and scholarly communication. Content analysis indicated a significant presence of topics from physics, computer science, and information technology within LIS research. Conclusions: This study highlights key trends and patterns in LIS research, with academic libraries, information literacy, LIS education, and librarians’ roles identified as critical areas for future exploration. Expanding databases and refining keyword searches are recommended to enhance knowledge dissemination and educational adaptability in the LIS field. The findings aim to support LIS researchers, facilitate research planning, and promote global interinstitutional cooperation